2020
DOI: 10.29252/rbmb.9.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Epigenetic Demethylation of NRF2, a Master Transcription Factor for Antioxidant Enzymes, in Colorectal Cancer

Abstract: Background: Epigenetic changes in CpG islands of the promoter regions of homeostasis-related genes, including nuclear factor erythroid 2-related factor 2 (NRF2), have been shown to hold a significant role in the development of colorectal cancer. Therefore, we aimed to examine the DNA demethylation pattern of the NRF2 promoter region in cancerous lesions from patients with colorectal cancer and the association of methylation status with clinicopathological features in the Iranian population. Methods: In this cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…Kopke demonstrated that by administering antioxidants prior to noise exposure can lower hearing thresholds and prevent cell death (26). In this study, we found that administering 100 mg or 200 mg of curcumin for 14 days before noise exposure resulted in a significant difference in mean SNR values following DPOAE and NRF2 expression in all groups.…”
Section: Discussionsupporting
confidence: 48%
“…Kopke demonstrated that by administering antioxidants prior to noise exposure can lower hearing thresholds and prevent cell death (26). In this study, we found that administering 100 mg or 200 mg of curcumin for 14 days before noise exposure resulted in a significant difference in mean SNR values following DPOAE and NRF2 expression in all groups.…”
Section: Discussionsupporting
confidence: 48%
“…Epigenetics changes mean gene function cannot be explained by changes in DNA sequences (1). These changes are inherited and do not affect the DNA nucleotide sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, demethylation of a CpG island in the promoter of NFE2L2 has been identified in CRC tumour samples. Whereas, the same site has been shown to be methylated in pre-cancerous colorectal polyps suggesting that the demethylation of NFE2L2 may influence carcinogenesis [271]. As KRAS and BRAF mutations are prevalent in CRC, NRF2 may frequently be upregulated by transcriptional activation of NFE2L2, as reported in mouse models of pancreatic cancer [164].…”
Section: Upregulation Of Nrf2 In Colorectal Tumoursmentioning
confidence: 97%